1993
DOI: 10.1111/j.1574-6968.1993.tb06488.x
|View full text |Cite
|
Sign up to set email alerts
|

Chemotaxis away from thiocyanic and isothiocyanic esters inPseudomonas aeruginosa

Abstract: Negative chemotaxis, the movement of organisms away from chemicals, was investigated in Pseudomonas aeruginosa using a rapid videotape method. Digital image processing was used to detect changes in bacterial numbers near the mouth of a capillary containing a test chemical. P. aeruginosa was found to be repelled by thiocyanic and isothiocyanic esters including allyl isothiocyanate, ethyl thiocyanate, methyl isothiocyanate and methyl thiocyanate. Particularly, the movement of bacteria away from methyl thiocyanat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2004
2004
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(2 citation statements)
references
References 12 publications
0
2
0
Order By: Relevance
“…As for NCS Ϫ , none of the reported studies could detect biological activities on the analyzed bacteria and fungi (15,32). On the other hand, a limited number of studies have demonstrated that bacteria belonging to Pseudomonas genus showed a negative chemotaxis to CH 3 SCN (33,34). Based on this finding, we hypothesized that CH 3 SCN synthesized by Arabidopsis also had biological activities toward bacteria.…”
Section: In Vitro Antibacterial Activities Of Ncsmentioning
confidence: 95%
“…As for NCS Ϫ , none of the reported studies could detect biological activities on the analyzed bacteria and fungi (15,32). On the other hand, a limited number of studies have demonstrated that bacteria belonging to Pseudomonas genus showed a negative chemotaxis to CH 3 SCN (33,34). Based on this finding, we hypothesized that CH 3 SCN synthesized by Arabidopsis also had biological activities toward bacteria.…”
Section: In Vitro Antibacterial Activities Of Ncsmentioning
confidence: 95%
“…The assignment of P. aeruginosa PAO1 chemoreceptors to their respective chemosensory pathways was reported by Ortega et al (10). thiocyanic esters (32,33). More recent work has brought insight into the molecular mechanisms involved and has led to the identification of many of the corresponding chemoreceptors (Table 1).…”
Section: Molecular Mechanisms and Chemoreceptors For Chemotaxismentioning
confidence: 80%